2017
DOI: 10.1002/casp.2318
|View full text |Cite
|
Sign up to set email alerts
|

Defining ethnic, national, and dual identities: Structure, antecedents, and consequences of multiple social identities of Turkish‐origin high school students in Germany

Abstract: The number of immigrants and children born to immigrant parents in Europe has risen steadily. Related to debates as to how best integrate immigrants, research points to the importance of investigating the structure as well as antecedents and consequences of immigrants' multiple identities. Here, we explore the relationship between three different identities endorsed by adolescent Turkish-origin immigrants in Germany: ethnic identity (i.e., Turkish identity), national identity (i.e., German identity), and dual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
69
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(77 citation statements)
references
References 32 publications
7
69
1
Order By: Relevance
“…Yet it is unlikely that the German context provides a more friendly intergroup climate as comparative studies that include Germany along with other European immigrant destinations reveal it to be among the least inclusive in terms of minorities' identification with the nation . Similarly, Martiny et al (2017) also found ethnic identification of Turkish-origin mid-adolescents to be negatively related to their German national identification.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Yet it is unlikely that the German context provides a more friendly intergroup climate as comparative studies that include Germany along with other European immigrant destinations reveal it to be among the least inclusive in terms of minorities' identification with the nation . Similarly, Martiny et al (2017) also found ethnic identification of Turkish-origin mid-adolescents to be negatively related to their German national identification.…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, Martiny et al . () also found ethnic identification of Turkish‐origin mid‐adolescents to be negatively related to their German national identification.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The significance of this work is that it suggests that diverse communities have an inherent positive effect on cross-ethnic friendship choices in young people; diversity propagates cross-ethnic friendship. Martiny et al (2017) bring together two lines of research, contact, and identity and advance our understanding of multiple identities in migrant children by showing the complex interplay of identity, contact, and integration. They explore how situational variables (in this case, intergroup contact) can shape identities, as well as examining the consequences of holding these identities for feelings of integration among Turkish-origin adolescents in Germany.…”
Section: Intergroup Contactmentioning
confidence: 96%
“…Consistent with this argument, cross‐sectional nonnetwork studies focusing on the role of the share of native friends for immigrants’ national identification have established a positive relationship between the two. This association has been found both for adults and adolescents in different countries such as Belgium (Agirdag et al., ), the Netherlands (De Vroome et al., ; De Vroome, Coenders, van Tubergen, & Verkuyten, ), Germany (Martiny, Froehlich, Deaux, & Mok, ; Schulz & Leszczensky, ), France (Sabatier, ), and Spain (Lubbers, Molina, & McCarty, ). However, due to their cross‐sectional nature, these studies do not allow for strong conclusions regarding the direction of causality; that is, they do not tell us whether native friends actually affected immigrants’ national identification or whether immigrants with strong national identification were more likely to befriend natives in the first place or whether both processes operate simultaneously.…”
Section: (How) Do Friends Influence Identification?mentioning
confidence: 88%